Answer:
Scrieți fracțile ordinare
Answer:
x = 10
y = 40
Step-by-step explanation:
60° + (2x + 7y)° = 180° because these two angles are supplementary
So 2x + y would be equal to 60°
60° + (2x + 7y)° = 180° subtract 60 from both sides
2x + 7y = 120 and
2x + y = 60 multiply second equation by -1 and it will be -2x -y = -60 now add it to first equation
2x + 7y -2x - y = 120 - 60 -2x will eliminate 2x
6y = 60 divide both sides by 6
x = 10
if 2x + y = 60 the we need to replace x with the value we found
2×10 + y = 60
y = 40
Answer:
Step-by-step explanation:
<em>Key Differences Between Covariance and Correlation
</em>
<em>The following points are noteworthy so far as the difference between covariance and correlation is concerned:
</em>
<em>
</em>
<em>1. A measure used to indicate the extent to which two random variables change in tandem is known as covariance. A measure used to represent how strongly two random variables are related known as correlation.
</em>
<em>2. Covariance is nothing but a measure of correlation. On the contrary, correlation refers to the scaled form of covariance.
</em>
<em>3. The value of correlation takes place between -1 and +1. Conversely, the value of covariance lies between -∞ and +∞.
</em>
<em>4. Covariance is affected by the change in scale, i.e. if all the value of one variable is multiplied by a constant and all the value of another variable are multiplied, by a similar or different constant, then the covariance is changed. As against this, correlation is not influenced by the change in scale.
</em>
<em>5. Correlation is dimensionless, i.e. it is a unit-free measure of the relationship between variables. Unlike covariance, where the value is obtained by the product of the units of the two variables.
</em>
You can find more here: http://keydifferences.com/difference-between-covariance-and-correlation.html#ixzz4qg5YbiGj
Answer:
d = 10.8167
Step-by-step explanation:
The distance between two points can be easily found by using the following expression
d = √((x1-x2)^2 + (y1-y2)^2)
where
(x1,y1) = (6,-4)
(x2,y2) = (0,5)
d = √((6-0)^2 + (-4-5)^2)
d = √(36 + 81)
d = √(117)
d = 10.8167
Answer:
The solutions are a₁ = -4/19 i, a₂ = 4/19 i and a₃ = -1/4
Step-by-step explanation:
Given the equation 76a³+19a²+16a=-4, for us to solve the equation, we need to find all the factors of the polynomial function. Since the highest degree of the polynomial is 3, the polynomial will have 3 roots.
The equation can also be written as (76a³+19a²)+(16a+4) = 0
On factorizing out the common terms from each parenthesis, we will have;
19a²(4a+1)+4(4a+1) = 0
(19a²+4)(4a+1) = 0
19a²+4 = 0 and 4a+1 = 0
From the first equation;
19a²+4 = 0
19a² = -4
a² = -4/19
a = ±√-4/19
a₁ = -4/19 i, a₂ = 4/19 i (√-1 = i)
From the second equation 4a+1 = 0
4a = -1
a₃ = -1/4